(untitled) (International Journal of Environmental Sciences, 2025)
Literature Review this study examines in depth the growing scientific interest in ergonomics approaches. In Indonesia, the majority of the population or people work in the agricultural sector. The application of the work environment and ergonomic machine tools will be massively used to realize a smart farming system (Smart Farming). The purpose of this literature review is to determine the contribution of ergonomics in the development and application of agricultural tools so that agricultural tools can be used according to the specifications and anthropometric needs of farmers. This article reviews 200 articles on Ergonomic Agricultural Tools from Google Scholar and Crossref from 2019-2024, using Publish or Perish and Vosviewer for data visualization. The results obtained are that there is a need for a conceptual discussion regarding the development of technology in ergonomic agricultural tools, realizing a smart farming system (Smart Farming), a discussion about the phenomenon of technological development of agricultural tools that are transforming rapidly and innovatively, and the need to discuss research development or testing. try developing agricultural tools in ergonomics interventions.